The effect of trace elements on the olivine-wadsleyite transformation - Gudfinnsson, G; Wood, B (1998)
Multianvil experiments were conducted at 1400 to 1600 °C on olivine and peridotite starting compositions to determine the partitioning of Ti, Al, Cr, Ni, Ca, and Na between coexisting olivine and wadsleyite. All of these elements occur as minor amounts in mantle olivine. Our experiments indicate that all, except Ca, partition preferentially into wadsleyite relative to olivine. The order of preference for wadsleyite is Ni